Neoadjuvant Chemoradiotherapy With Simultaneous Integrated Boost in Locally Advanced Cervical Cancer: Long Term Results of a Single-Center Experience - Nardangeli, Alessia; Autorino, Rosa; Boldrini, Luca; Campitelli, Maura; Reina, Sara; Ferrandina, Gabriella; Bizzarri, Nicolò; Tagliaferri, Luca; Macchia, Gabriella; Valentini, Vincenzo; Gambacorta, Maria Antonietta (Frontiers in Oncology, 2022)
Aim of this study was to analyze the efficacy and tolerability of simultaneous integrated boost volumetric modulated arc therapy (SIB-VMAT) associated to cisplatin-based chemotherapy in preoperative setting of patients with locally advanced cervical cancer (LACC). From June 2013 to September 2019, we analyzed patients with LACC undergone to neoadjuvant chemoradiation (CRT). A radiation dose of 39.6 Gy, 1.8 Gy/fraction, was delivered to the pelvis plus a radiation dose to the primary tumor delivered with SIB-VMAT strategy for a total of 50.6Gy, 2.3Gy/fraction in 25 fractions. Cisplatin-based chemotherapy was delivered associated to radiotherapy. Radical hysterectomy plus pelvic with or without aortic lymphadenectomy was performed within 7 to 8 weeks from CRT. One hundred and forty-eight patients (median age: 49.5 years; FIGO stage IB2: 7, IIA: 8, IIB: 106, IIIA: 5; IIIB: 16; IVA: 5, IVB: 1; N0: 56, N1: 92) were analyzed. The treatment was well tolerated with a good compliance: no grade 3/4 gastrointestinal or genitourinary toxicity were reported; grade 3 neutropenia was described in 5 cases. Pathological complete response (pCR) was documented in 68 cases (46%) and 32 patients (21.6%) had a microscopic residual disease. Pathological nodal involvement was observed in 23 pts (15.5%). At median follow-up of 59 months (range: 27-100), the 3-years local control was 78.5%, whereas the 3-years metastasis-free survival was 70.5%. The 3-years overall survival rate was 89.0%. Neoadjuvant CRT with SIB-VMAT followed by radical surgery results in a high rate of pathologically assessed complete response and a very encouraging local control rate, with acceptable toxicity.